Implementasi Pembelajaran PJOK Pada Masa Pandemi Covid-19 di Sekolah Dasar - Bustanol Arifin; Falistya Roisatul Mar’atin Nuro; Abdurrohman Muzakki; Lujeng Ikhlasatul Riska (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
The existence of the Covid-19 pandemic has resulted in changes in all aspects of life including aspects of education in Indonesia. Learning that is usually carried out in schools turns into at-home online. PJOK learning provides learning experiences to students in the form of physical activities, play, and exercise that are planned systematically to stimulate physical growth and development, motor skills, thinking skills, emotional, social, and morals. The purpose of this study is to describe the implementation of PJOK learning during the Covid-19 pandemic in elementary schools including planning, implementation, and evaluation. The research subject consisted of 25 students and teachers of class III of SDN Wirogunan Pasuruan City. The research method used is qualitatively descriptive. Data collection techniques through interviews, observations, and documentation. The results showed that the PJOK learning process was carried out online